Use of insulin pump therapy is associated with reduced hospital-days in the long-term: a real-world study of 48,756 pediatric patients with type 1 diabetes - Auzanneau, Marie; Karges, Beate Maria; Neu, Andreas; Kapellen, Thomas Michael; Wudy, Stefan A.; Grasemann, Corinna; Krauch, Gabriele; Gerstl, Eva-Maria; Däublin, Gerhard; Holl, Reinhard W. (European journal of pediatrics, 2021)
In pediatric diabetes, insulin pump therapy is associated with less acute complications but inpatient pump education may lead to more hospital days. We investigated the number of hospital days associated with pump vs. injection therapy between 2009 and 2018 in 48,756 patients with type 1 diabetes < 20 years of age from the German Diabetes Prospective Follow-up Registry (DPV). Analyses were performed separately for hospitalizations at diagnosis (hierarchical linear models adjusted for sex, age, and migration), and for hospitalizations in the subsequent course of the disease (hierarchical Poisson models stratified by sex, age, migration, and therapy switch). At diagnosis, the length of hospital stay was longer with pump therapy than with injection therapy (mean estimate with 95% CI: 13.6 [13.3-13.9] days vs. 12.8 [12.5-13.1] days, P < 0.0001), whereas during the whole follow-up beyond diagnosis, the number of hospital days per person-year (/PY) was higher with injection therapy than with pump therapy (4.4 [4.1-4.8] vs. 3.9 [3.6-4.2] days/PY), especially for children under 5 years of age (4.9 [4.4-5.6] vs. 3.5 [3.1-3.9] days/PY).
Gesehen am 14.04.2021
Published online: 1 December 2020